PENGUJIAN SUBSTANTIF ATAS AUDIT ASET TETAP PT AZS OLEH KAP JOACHIM ADHI PITER POLTAK & REKAN - Abeliwa Zulfan Sukses Billiton Putra Islami (2022)
This final project report discusses the substantive testing of the audit of PT AZS's fixed assets by the Public Accounting Firm of Joachim, Adhi, Piter, Poltak & Partners. PT AZS is a company engaged in the Real Estate sector which has fixed assets in the form of buildings, equipment, and vehicles. Therefore, the processing of fixed assets will affect the fairness of the financial statements. Based on the results of the substantive test, the auditor knows that in carrying out the audit at PT AZS, it has been in accordance with the predetermined audit plan. Some of the related accounts are fixed asset accounts, depreciation expense, and accumulated depreciation. The audit finding at PT AZS is to record a fixed asset to the inventory category which should be part of equipment assets.